Recent Advances in Nanophotonics Fundamentals and Applications - Kahrizi, Mojtaba; Sohi, Parsoua A. (IntechOpen, 2020)
This volume brings together several recent research articles in the field of nanophotonics. The editors have arranged the chapters in three main parts: quantum devices, photonic devices, and semiconductor devices. The chapters cover a wide variety of scopes in those areas including principles of plasmonic, SPR, LSPR and their applications, graphene-based nanophotonic devices, generation of entangled photon and quantum dots, perovskite solar cells, photo-detachment and photoionization of two-electrons systems, diffusion and intermixing of atoms in semiconductor crystals, lattice and molecular elastic and inelastic scattering including surface-enhanced Raman Scattering and their applications. It is our sincerest hope that science and engineering students and researchers could benefit from the new ideas and recent advances in the field that are covered in this book.